ChemInform Abstract: Direct Asymmetric Dearomatization of 2‐Naphthols by Scandium‐Catalyzed Electrophilic Amination. Issue 26 (June 2015) - Nan, Jiang; Liu, Jingjing; Zheng, Huayu; Zuo, Zhijun; Hou, Lei; Hu, Huaiming; Wang, Yaoyu; Luan, Xinjun
Abstract Catalytic asymmetric aminative dearomatization of 1‐substituted 2‐naphthols is successfully implemented with electrophilic azodicarboxylates under the catalysis of chiral ScIII/pybox complexes.